The Role of Economics in Islamic Education Marketing: Strategies for Building Public Trust and Loyalty - Mohammad Abdul Aziz Al Wahedi; Rausyan Fikri; Annisa Tri Ananda Dewi; Moh. Mohlas; Muthi’ah Rahman; Maulidia Adzimah (Educazione: Journal of Education and Learning, 2024)
This study examines the role of economics in shaping effective marketing strategies for Islamic educational institutions, particularly in building public trust and long-term loyalty. The increasing competition among educational providers and the growing expectations of Muslim communities necessitate a strategic integration of economic principles with Islamic values. This research aims to analyze how value-based marketing, transparency, and Islamic branding contribute to trust formation and loyalty sustainability. Employing a non-empirical design, the study adopts a conceptual and theoretical approach through a systematic review of relevant literature in Islamic marketing, educational management, and behavioral economics. The analytical framework integrates theories of Islamic marketing ethics, experiential marketing, and institutional trust to construct a comprehensive model. The findings indicate that the incorporation of Sharia-compliant marketing principles, supported by transparency and accountability, strengthens institutional credibility and enhances stakeholder engagement. Furthermore, the study highlights that trust acts as a mediating variable linking marketing strategies to long-term loyalty, while consistent value delivery ensures sustainability. The discussion emphasizes the importance of aligning economic strategies with religious and cultural expectations to achieve competitive advantage. These insights contribute to the development of a more ethical and sustainable marketing paradigm in Islamic education.